Hemelvaartsdag. V.l.n.r.: Van Twist, Plesman, Spee, Van Es, Radisneki, Suikerbuik . Origineel in rijksarchief Noord-Brabant (1935)
Hemelvaartsdag. V.l.n.r.: Van Twist, Plesman, Spee, Van Es, Radisneki, Suikerbuik . Origineel in rijksarchief Noord-Brabant.